2009
DOI: 10.1111/j.1095-8312.2009.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial introgression and replacement between yellowhammers (Emberiza citrinella) and pine buntings (Emberiza leucocephalos) (Aves: Passeriformes)

Abstract: In studies of phylogeography and taxonomy, strong emphasis is usually placed on the study of mitochondrial (mt)DNA. In the present study, we present a remarkable case in which highly phenotypically divergent species have almost no divergence in mtDNA. Yellowhammers (Emberiza citrinella Linnaeus) and pine buntings (Emberiza leucocephalos S. G. Gmelin) differ noticeably in appearance and song but hybridize in some areas of contact. They share a variety of closely-related mtDNA haplotypes, with little divergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
99
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 66 publications
11
99
1
Order By: Relevance
“…Females being the heterogametic sex in birds, Haldane's rule would also predict that mitochondrial haplotypes show patterns of reduced introgression compared with nuclear alleles (Carling and Brumfield, 2008). However, several cases of interspecific gene flow documented in birds depicted the reverse pattern; no nuclear introgression is detected while the maternally transmitted mtDNA exhibits high levels of introgression (Tejedor et al, 2007;Bellemain et al, 2008;Irwin et al, 2009). This is the same pattern we observed between the North American L. marinus and the sympatric L. smithsonianus.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Females being the heterogametic sex in birds, Haldane's rule would also predict that mitochondrial haplotypes show patterns of reduced introgression compared with nuclear alleles (Carling and Brumfield, 2008). However, several cases of interspecific gene flow documented in birds depicted the reverse pattern; no nuclear introgression is detected while the maternally transmitted mtDNA exhibits high levels of introgression (Tejedor et al, 2007;Bellemain et al, 2008;Irwin et al, 2009). This is the same pattern we observed between the North American L. marinus and the sympatric L. smithsonianus.…”
Section: Resultssupporting
confidence: 72%
“…Indeed, one general pattern that emerges from recent studies is that introgression rates among loci may greatly vary according to their location in the genome. In particular, several studies have reported cases of mitonuclear discordances with introgression of mitochondrial DNA and low or even apparent absence of nuclear introgression (fish: Wilson and Bernatchez, 1998, birds: Bellemain et al, 2008;Irwin et al, 2009, mammals: Roca et al, 2005Good et al, 2008;Melo-Ferreira et al, 2009, amphibians: ZieliƄ ski et al, 2013. The reverse situation, high nuclear introgression with low mitochondrial introgression or lack of mitochondrial introgression has also been observed in butterflies, a primate species and birds species (Steeves et al, 2010, see also Petit and Excoffier, 2009 for a review).…”
mentioning
confidence: 99%
“…In these cases, significantly less mtDNA divergence compared with nuclear differentiation can implicate mitochondrial introgression between taxa (e.g. Cathey et al 1998;Bachtrog et al 2006;Irwin et al 2009). …”
Section: Methodsmentioning
confidence: 99%
“…For example, asymmetrical mtDNA introgression may be caused by local adaptation, mtDNA-nDNA coevolution or selective sweeps of universally favoured mutations (Irwin et al, 2009). The lack of obvious environmental gradients geographically coincident with this zone of secondary contact (Williams, 2009) and our use of putatively neutral loci does not support the local adaptation hypothesis.…”
Section: Discussionmentioning
confidence: 70%